A Study of Indian Secondary Science Teachers’ Current Orientations toward Teaching Science: Exploring the misalignment between teaching orientations and classroom practice among Indian secondary science teachers (Journal of Advances and Scholarly Researches in Allied Education, 2019)
National Curriculum Framework aims to provide a more constructivist approach to learning in all topics. Teachers' attitudes toward teaching and learning are critical to the success of curriculum change in other countries (e.g., the United States), according to previous studies. Accordingly, we decided to investigate Indian secondary science teachers' teaching orientations through an examination of two teachers' practises and how these are mirrored in their teaching orientations. As a result of their many external limitations, we found that teachers' orientations agreed with the goals of reform, but their classroom practise did not. This may have been due to the many restraints that teachers felt were placed on them. We examine the implications of these findings for professional development that take into consideration alignment for all three components while taking into account probable cultural barriers.